Critical thinking in undergraduate general nursing students - Noone, Thomas F. (Trinity College (Dublin, Ireland). School of Education, 2015)
This study investigated critical thinking in general nursing students registered in a four year undergraduate BSc. Honours degree course in nursing, at two university sites in Ireland. A main aim was to find out the critical thinking dispositions and skills of first and third year undergraduate nursing students. The second aim was to find out if there was a difference in the critical thinking dispositions and skills of the first year cohort compared to the third year cohort of nursing students.
Embargo End Date: 2020-08-08
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin, 2015